Immunological mechanisms in Meniere’s disease - Yuan, Vincent G.; Xia, Anping; Santa Maria, Peter L. (Frontiers in Immunology, 2025)
Meniere’s disease (MD) is a chronic, relapsing inner ear disorder characterized by episodes of vertigo, fluctuating sensorineural hearing loss, tinnitus, and aural fullness. Although its etiology has long remained elusive, accumulating evidence implicates immune dysregulation as a central contributor to disease pathogenesis, particularly in patients who do not respond to standard therapies. This review synthesizes current insights into the immunopathological mechanisms underlying MD, focusing on the roles of both innate and adaptive immune cells—including macrophages, dendritic cells, T cells, and B cells—in promoting inflammation, endolymphatic hydrops, and sensory dysfunction. We examine the contribution of these immune cells to tissue damage, along with the roles of cytokine signaling and immune complex deposition. Emerging immunotherapies, including corticosteroids, biologics, and inflammasome inhibitors, are evaluated for their therapeutic potential. The review also highlights promising directions in precision medicine, such as immune profiling, biomarker discovery, and stratified clinical trials aimed at personalizing treatment. By integrating recent immunological advances with clinical management strategies, we underscore the potential of immune guided approaches to transform the diagnosis, treatment, and long-term care of patients with MD.